Inductive and Mechanistic Studies of Oxidation of Carboxylic and Hydroxy-carboxylic Acids in Fe(II)-Mn(VII) Reaction: Effect of Manganese(II) - P. Dhabre, Ramrao; Madhava Rao, B. (Asian Journal of Chemistry, 2010)
An attempt is made to explore the mechanism of induced oxidation of carboxylic and hydroxy-carboxylic acids in Fe(II)-M(VII) redox reaction. The manganese(VII)-carboxylic acid reactions induced by iron(II) may involve the participation of Mn(VI), Mn(IV) and Mn(III) as transient species. The probable mechanism is that Mn(VI) formed in the primary step by one equivalent process, oxidises the carboxylate ion to a ketonic product along with the formation of Mn(IV). The intermediate Mn(IV) also oxidises the carboxylate ion to a ketonic product with the formation of Mn(III).